Strategi Humas Dalam Mengembalikan Citra Positif Radio Baiturrahman Di Kalangan Pendengar - Dara Julana; Hafidhatul Maula Ali (Sadida Islamic Communications and Media Studies, 2021)
Baiturrahman Radio among Listeners" was conducted to find out what strategies were carried out by public relations at Baiturrahman Radio to restore a positive image among the public. This study uses a research method in the form of a descriptive method using field research techniques. Data collection techniques using observation, interviews and documentation. This study also uses a descriptive correlation method using a quantitative approach, namely describing the Public Relations Strategy in Restoring a Positive Image of Baiturrahman Radio among Listeners. This research approach is used to test the applied hypothesis. This research uses Situational Theory of The Publics. The situational theory of the publics or commonly abbreviated as STP is a useful theory for identifying the public, so that it can create more specific public categories based on the communication behavior of individuals and the effects of communication received by the individual. The results showed that the strategy carried out by Baiturrahman Radio's publicist was to re-schedule the Dakwatul Islam program so that the message conveyed was not maximal and no longer fragmented due to the call to prayer schedule which changes every day.